Preoperative Measurement of ACL Insertion Sites - Schwartzberg, Randy; Snyder, Kevin; Reuss, Bryan (The Journal of Knee Surgery, 2015)
This study was designed to evaluate preoperative predictions of the femoral and tibial ACL insertion lengths. Intraoperative measurements were made of the femoral and tibial ACL insertion lengths with an arthroscopic ruler. A musculoskeletal radiologist and a sports medicine orthopedic surgeon measured the ACL insertions from preoperative magnetic resonance imagings (MRIs) in a blinded fashion. Correlations between height, weight, body mass index, and gender with intraoperative ACL insertion length measures were also evaluated. Patient height and male gender demonstrated strong correlations with intraoperative ACL insertion measures. A moderate correlation was seen between patient weight and intraoperative ACL insertion measures. When evaluating the frequency with which the raters' respective MRI measures were exactly the same as the intraoperative measures, moderate correlations were seen. The radiologist and orthopedic surgeons' MRI measures were within 3 mm of the intraoperative measures 98 and 75% of the time, respectively, for the femur and 92 and 83% of the time, respectively, for the tibia. This study concludes that preoperative MRI measures of ACL insertion lengths can be used to predict intraoperative ACL insertion lengths. Also, it is expected that taller patients and male patients should have greater ACL insertion lengths seen arthroscopically.
Keywords: ACL insertions; double-bundle ACL reconstruction; anatomic ACL reconstruction